Design of hydrofoil for the resistance improvement of planing boat based on CFD technology. (1st July 2022) - Shen, Hailong; Xiao, Qing; Zhou, Jin; Su, Yumin; Bi, Xiaosheng
Abstract: The purpose of this study was to design a hydrofoil which would improve boat performance through enhanced resistance reduction. Commercial CFD code STARCCM+ was used to solve the Unsteady Reynolds Averaged Navier Stokes Equations for the flow around the boat. Uncertainity study is conducted in order to obtain an effective and reliable numerical calculation method. The method was then validated by direct comparison of the numerical data at different speeds with the test data of USV01 planing boats. Accordingly, twelve hydrofoil design cases were considered, and their resistance reduction performance at 8 m/s was predicted and compared with each other through the numerical calculation method. Effects of hydrofoil parameters such as longitudinal installation position, span, attack angle, installation height on the resistance reduction performance were investigated. One of 12 cases was chosen to investigate the resistance reduction effect of hydrofoil at different speeds. The results show that the hydrofoil, with proper installation position and design parameters, has a significant resistance reduction effect. At 8 m/s, the hydrofoil designed in this paper can reduce boat resistance by up to 30.74%.To analyze the principle of hydrofoil, the flow field around hull and hydrofoil was numerically simulated and studied. Highlights: The hydrofoils designed in this paper all had a significant resistance reduction effect at the boat design speed of 8m/s. The maximum reduction of resistance was 30.74% of the total resistance of the bare planing boat. The current research illustrates that after installing the hydrofoil, the planing boat had a significant resistance reduction effect within the speed range of the real boat speed of 23.33 knots to 38.87 knots. The hydrofoil could not always achieve the resistance reduction effect in the entire speed range of the planing boat. The influence of hydrofoil on the flow field around the hull, especially the velocity field, is analyzed numerically.